Carbon smart agriculture: An integrated regional approach offers significant potential to increase profit and resource use efficiency, and reduce emissions. (1st February 2021) - Maraseni, Tek; An-Vo, Duc-Anh; Mushtaq, Shahbaz; Reardon-Smith, Kate
Abstract: Climate change is a multifaceted problem impacting social, economic and environmental values. Strategies to reduce climate change impacts require novel and integrated solutions that simultaneously benefit multiple parts of society and minimise potential conflict between economic, food production and environmental values. Here, we use a novel integrated analysis of the energy-water-food nexus, land use, and climate change to explore whether mounting environmental pressure can be reversed without negative consequences on food production and economic outcomes. Using Australia as a test case, our results show the significant potential of optimal use of land and water resources in achieving both increased crop production and reduced greenhouse gas (GHG) emissions while sustaining economic outcomes. Our trade-off analysis shows that, at a regional level, up to 50% reduction in GHG emissions from irrigated crop production is possible without compromising total gross margins; in addition, regional optimisation of resource use resulted in surplus water and land available for environmental planting. Our analysis also indicates that further emissions reduction without trade-offs can be achieved with a higher carbon price and/or where water markets ensure higher value water use. To our knowledge, this is the first future-looking modelling to integrate this range of crop production, environmental and economic issues. This type of integrated approach has potential to better inform government emissions reduction policy aimed at finding an equitable and sustainable balance across multiple policy areas. Highlights: Develops an integrated regional water-food-GHG nexus optimisation model. Includes systematic evaluation of externalities such as carbon and water policies. Optimal use of land and water can increase crop production whilst reducing carbon footprints. At a price of $30/tCO2e, ∼50% emissions reduction is possible without reducing income. Adoption of the approach would have implications for sustainability at a range of scales.